Islamic law in past and present - Rohe, Mathias, 1959- (Themes in Islamic Studies, 2015)
Islamic Law in Past and Present , written by the lawyer and Islamicist Mathias Rohe, is the first comprehensive study for decades on Islamic law, legal theory, reform mechanisms and the application of Islamic law in Islamic countries and the Muslim diaspora. It provides information based on an abundance of Oriental and Western sources regarding family and inheritance law, contract and economic law, penal law, constitutional, administrative and international law. The present situation and 'law in action' are highlighted particularly. This includes examples collected during field studies on the application of Islamic law in India, Canada and Germany.